1997
DOI: 10.1007/s004390050375
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution comparative hybridization to combed DNA fibers

Abstract: Comparative genomic hybridization (CGH) has proven to be a comprehensive new tool to detect genetic imbalances in genomic DNA. However, the resolution of this method carried out on normal human metaphase spreads is limited to low copy number gains and losses of > or = 10 Mb. An improved resolution allowing the detection of copy number representations of single genes would strongly enhance the applicability of CGH as a diagnostic and research tool. This goal may be achieved when metaphase chromosomes are replac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…These methods allow for the genome-wide characterization of aneupoloidies with a resolution of about 1 Mb (9, 10). Recent studies suggest that CGH eventually could be used to detect copy number alterations of single genes by using arrays of cloned DNA on a diagnostic chip, but the ability to reliably quantify subtle alterations on the kilobase scale has proven to be technically difficult (11)(12)(13). Fiber-FISH techniques have advanced the resolution of chromosomal analysis to the kilobase range.…”
mentioning
confidence: 99%
“…These methods allow for the genome-wide characterization of aneupoloidies with a resolution of about 1 Mb (9, 10). Recent studies suggest that CGH eventually could be used to detect copy number alterations of single genes by using arrays of cloned DNA on a diagnostic chip, but the ability to reliably quantify subtle alterations on the kilobase scale has proven to be technically difficult (11)(12)(13). Fiber-FISH techniques have advanced the resolution of chromosomal analysis to the kilobase range.…”
mentioning
confidence: 99%
“…FISH using cosmid probes has been widely used to give increased resolution when detecting deletions and duplications [Petrij et al, 2000;Voskova-Goldman et al, 1997;Worley et al, 1995;Faivre et al, 2000]. The resolution of cytogenetic techniques has been further improved by using combed cosmid fibers as targets for CGH [Kraus et al, 1997] andFISH [fiber FISH, van de Rijke et al, 2000], although they remain labor intensive compared to standard molecular genetic techniques.…”
Section: Cytogenetic Methodsmentioning
confidence: 99%
“…Estimates of gene dosage have typically been based on comparisons with a reference standard; absolute (i.e., molar) quantitation has been reported by the inclusion of known quantities of PCR competitor. Other approaches, including the study of junction fragments or microsatellite inheritance, and, more recently, long accurate PCR [CoulterMackie et al, 1998], fluorescent in situ hybridization (FISH) [Pemble et al, 1994;Brockmoller et al, 1992], comparative genomic hybridization (CGH) [Bentz et al, 1998;Kraus et al, 1997;Pinkel et al, 1998], and array-CGH [Pollack et al, 1999] have also been employed. In some cases, knowledge of the gene (or exon) dosage may not be sufficient to establish the pathogenic consequences of a genotype, as for example in spinal muscular atrophy, where gene duplications and unstable regions of the genome can complicate the issue [Parsons et al, 1998].…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports from two groups have addressed these needs by substituting for the target metaphase chromosomes in the CGH protocol. Kraus et al 68 demonstrated the use of a 'molecular combing' procedure to stretch DNA fibres and adhere them to a glass slide for use as a target. For these model experiments, different ratios of cosmid probes were labelled and hybridized to combed, linearized cosmid fibres and the resulting FRs measured and compared with expected results.…”
Section: Future Prospectsmentioning
confidence: 99%